Professional Learning Opportunities for Teacher Candidates - Victoria N Seeger; Chad Boyles (Educational Considerations, 2021)
Using a case study model, the research explored how teacher candidates viewed professional learning, its impact on undergraduate preparation for the teaching profession, and what kind of role it was perceived to play by early-career teachers. Research participants responded to questions about how the professional learning impacted their views on preparation for teaching, how experiences influenced discussions with interviewers prior to being hired, and how professional learning prepared them for interacting with colleagues and administrators. The participants’ perceptions were explored through surveys and focus groups.
Keywords: professional learning; teacher candidates; teacher preparation; new teachers